RESEPSI PEMBACA TERHADAP CERPEN HASHIRE MEROSU KARYA DAZAI OSAMU - Fajria Noviana (Diponegoro University, 2017)
This paper attempt to describe about the use of literary reception method to find out readers’ responses on Dazai Osamu’s short story “Hashire Merosu”. Issues to be discussed are limited to some elements that built the structure of this short story. Those elements are character, setting, theme, and moral of the story. Respondents are Japanese Study Program’s 2nd year students. Difficulty level of this short story’s Japanese is about N4 and N3 on Japanese Language Proficiency Test level. The result is, as amateur readers, respondents can understand the story and can analyze elements that built the structure of this short story in simple way.